Adaptive immunity to SARS-CoV-2. Issue 1 (9th July 2020) - Altmann, Daniel M
Abstract: The majority of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 exposed individuals mount an antibody response within around 2-weeks and spike antigen-binding responses correlate well with functional virus neutralization. A minority makes little detectable antibody, generally those with either very mild/asymptomatic disease or those with severe/lethal infection. However, in general, antibody titre correlates with viral load and duration of exposure. There is evidence for cross-reactivity with the other human coronaviruses, though the functional impact of this is as yet unclear. Therapeutic use of neutralizing monoclonal antibodies offers potential for clinical use. While there is evidence for neutralizing antibody as a correlate of protection, some cases indicate the potential for full recovery in the absence of antibody. Studies of T-cell immunity following acute infection show CD4 and CD8 responses to epitopes across diverse viral antigens, possible cross-reactivity with epitopes from the common cold human coronaviruses and large-scale activation. However, in severe cases, there is evidence for T-cell lymphopaenia as well as expression of exhaustion markers. Analysis of serum biomarkers of disease severity implicates a hyperinflammatory contribution to pathogenesis, though this has not been mechanistically delineated beyond a likely role of raised IL-6, considered a therapeutic target. Despite rapid progress, there remain pressing unknowns. It seems likely that immune memory to SARS-CoV-2 may be relatively short lived, but this will need longitudinal investigation. Also, this is a disease of highly variable presentation and time course, with some progressing to protracted, chronic symptoms, which are not understood. The contribution of immunopathological mechanisms to tissue damage, whether in the lung, kidney, heart or blood vessels, is unclear. The immunology underlying the differential susceptibility between the very young and the very old is unresolved, a question with ramifications for vaccine roll-out. The greatest challenge relates to rapid generation, testing and manufacture of vaccines that are immunogenic, protective (at least from symptomatic disease) and safe—a challenge that looks achievable.